2001
DOI: 10.1046/j.1464-410x.2001.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

A combined analysis of double‐blind trials of the efficacy and tolerability of doxazosin‐gastrointestinal therapeutic system, doxazosin standard and placebo in patients with benign prostatic hyperplasia

Abstract: Objective To report an integrated analysis of two previous studies fully characterizing the clinical utility of the controlled-release gastrointestinal therapeutic system (GITS) formulation of doxazosin in the treatment of benign prostatic hyperplasia (BPH). Patients and methods Two pivotal randomized, doubleblind studies of doxazosin GITS for BPH were assessed by an integrated analysis. Both studies included a 2-week washout period, a 2-week single-blind placebo run-in phase, and a 13-week double-blind treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 21 publications
8
62
1
4
Order By: Relevance
“…The QoL had decreased by 1.0 point compared with the baseline in patients with ED, whereas in non-ED group, it decreased by 1.9 points. This result was consistent with previous studies findings of significant reductions in total IPSS and QoL, and substantial increases in npg Q max with doxazosin [7,8]. In both studies, the α1-adrenoceptor antagonists improved symptom scores by 35%-40% vs. baseline and Q max by 16%-26% vs. baseline for 3 months of treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The QoL had decreased by 1.0 point compared with the baseline in patients with ED, whereas in non-ED group, it decreased by 1.9 points. This result was consistent with previous studies findings of significant reductions in total IPSS and QoL, and substantial increases in npg Q max with doxazosin [7,8]. In both studies, the α1-adrenoceptor antagonists improved symptom scores by 35%-40% vs. baseline and Q max by 16%-26% vs. baseline for 3 months of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in our study, doxazosin produced significant improvements at the sixth week of treatment. Our results are similar to Kirby et al [7] who reported an analysis of doubleblind trials of the efficacy and tolerability of doxazosin. In that study, although the differences between the mean changes of IPSS and Q max in doxazosin groups and placebo were significant, the mean change in placebo group over baseline was also significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In trials of doxazosin GITS and doxazosin standard in patients with BPH, 21,22 both formulations were shown to significantly improve the symptoms of BPH, as shown by a 45% reduction for each in total IPSS from baseline to final visit, compared with a 34% reduction in patients taking placebo. Doxazosin GITS and doxazosin standard produced comparable improvements in Q max that were significantly greater than with placebo, with a greater improvement sooner after treatment with doxazosin GITS than with doxazosin standard.…”
Section: Doxazosin Gits In Bphmentioning
confidence: 99%
“…Doxazosin GITS is as effective as standard doxazosin in the treatment of hypertension [16][17][18][19][20] or BPH. 18,[21][22][23] Although the blood pressure-lowering effect of doxazosin is a therapeutic advantage in patients with comorbid BPH and hypertension, it has been erroneously perceived as less desirable in normotensive men. However, the degree of blood pressure lowering with doxazosin differs markedly in hypertensive and normotensive patients.…”
Section: Introductionmentioning
confidence: 99%